Cross-Disciplinary Thematic Special Series: Special Education and Mathematics Education. (November 2016) - Xin, Yan Ping; Tzur, Ron
This article introduces the thematic special series on intersection of mathematics education and special education. This special series will include four research papers and one commentary. The four research papers rooted in a working group from the annual conferences of the International Group of the Psychology of Mathematics Education (PME) as well as its North American Chapter (PME-NA).